Security and Privacy Issues Related to Electronic Documents based on the Public Perception - Farhana Islam (Journal of Informatics Education and Research, 2025)
This paper aims to investigate the security issues and risks to privacy associated with electronic documents (e-documents) within an organization. This paper also emphasis on new technologies applied to documents and document handling. Electronic Document encourages significant improvements in productivity and performance. A Document Management System (DMS) typically refers to the use of a computer system and software to store, organize, and manage electronic records and scanned versions of paper documents. This paper explains the ways in which the security and privacy of users are maintained when they access electronic documents through sharing or use. According to the public perception the dimensions of the security and privacy measurement are selected. This paper through answering the research questions, describes the measures that companies are maintaining privacy and security to preserve e-business document confidentiality. It also discusses the public perception of e-document privacy and security. In the conclusion, further recommendations specify how the firms should make a balance between the privacy and security issues in their e-documents.